A Literature Review of Critical Components and International Success Factors of Green Public Procurement: Lessons for Nepal from Global Practices - Pokhrel, Adarsha; Awasthi, Keshab Datt (Journal of UTEC Engineering Management, 2025)
Green Public Procurement (GPP) is gaining recognition as a strategic policy instrument for aligning public spending with environmental and sustainability objectives. Although numerous nations have formalized GPP via legal, market, and capacity-building frameworks, Nepal remains in the initial phase of implementation. This research seeks to pinpoint the essential elements and global success factors of GPP, extracting insights that can guide policy and practice in Nepal. This study relies entirely on an extensive literature review, including both national and international policy papers, organizational protocols, case studies, and chosen peer-reviewed scholarly sources. The review combined insights from various countries with established GPP frameworks, highlighting common structural elements, facilitating factors, and contextual obstacles pertinent to Nepal. The literature review pinpointed six fundamental elements crucial for successful GPP: (1) strong policy and legal structures, (2) strategic planning and prioritization, (3) stakeholder involvement and cooperation, (4) execution and capacity enhancement, (5) monitoring, assessment, and openness, and (6) political commitment and leadership. International key success factors comprise life-cycle costing, policy harmonization among agencies, specific supplier incentives, and the incorporation of sustainability into procurement regulations. Lessons for Nepal highlight the importance of institutional dedication, market preparedness for sustainable goods, and well-defined performance metrics. Results emphasize that effective GPP execution necessitates a unified strategy integrating legislative changes, skill enhancement, and market support. By embracing proven global strategies and tailoring them to local institutional, economic, and market contexts, Nepal could hasten the incorporation of sustainability into public procurement. The research wraps up with suggestions for policymakers to create explicit mandates, strengthen stakeholder capabilities, and improve monitoring systems to ensure procurement aligns with national sustainable development goals.